Mentorship-driven talent management : the Asian experience. - Kumar, Payal (Emerald Publishing Limited, 2020)
Evidence suggests that research on mentorship has been dominated by the West, and little is known about the cultural variations of the mentoring phenomenon. This book aims to provide a deeper understanding of the contextual interpretation of mentoring by focusing on the Asian experience in countries such as China, India, Korea and Taiwan.